Effectiveness of Intravenous Immunoglobulin for Management of Pain in Patients with Postpolio Syndrome - Min Cheol Chang; Jin-Sung Park; Jong-moon Hwang; Donghwi Park (Pain Research and Management)
Objective. Many patients with postpolio syndrome (PPS) experience pain. In this study, we aimed to review previous studies to investigate the effectiveness of intravenous immunoglobulin (IVIG) for managing pain in patients with PPS. We performed a narrative review. Methods. In PubMed, we searched for the keywords ((Immunoglobulin OR IVIG) AND (poliomyelitis OR poliomyelitis syndrome)). We included articles in which IVIG was infused in patients with PPS and pain severity was measured before and after treatment. Results. In the results, five articles (4 randomized controlled trials and 1 prospective observational study) were included in this review. Four of the studies reported that IVIG had a positive pain-reducing effect in patients with PPS. In addition, 4 studies evaluated the outcomes related to muscle strength and function. Of these studies, 3 showed some improvement in measurements for muscle strength and function. Conclusion. In conclusion, IVIG might be one of the beneficial options for managing pain in PPS. Pain reduction might be responsible for the improvement of muscle strength or function. To confirm the benefits of IVIG in reducing pain, more high-quality studies are required.